Programming Visual Illusions for Everyone - Bertamini, Marco (Vision, Illusion and Perception,, 2018)
If you find visual illusions fascinating Programming Visual Illusions for Everyone is a book for you. It has some background, some history and some theories about visual illusions, and it describes in some detail twelve illusions. Some are about surfaces, some are about apparent size of objects, some are about colour and some involve movement. This is only one aspect of the book. The other is to show you how you can create these effects on any computer. The book includes a brief introduction to a powerful programming language called Python. No previous experience with programming is necessary. There is also an introduction to a package called PsychoPy that makes it easy to draw on a computer screen. It is perfectly ok if you have never heard the names Python or PsychoPy before. Python is a modern and easy-to-read language, and PsychoPy takes care of all the graphical aspects of drawing on a screen and also interacting with a computer. By the way, both Python and PsychoPy are absolutely free. Is this a book about illusions or about programming? It is both!